2004
DOI: 10.1023/b:clin.0000024740.44602.b7
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D expression levels in nongynecological solid tumors: Clinical and therapeutic implications

Abstract: Cathepsin D is a lysosomal acid proteinase which is involved in the malignant progression of breast cancer and other gynecological tumors. Clinical investigations have shown that in breast cancer patients cathepsin D overexpression was significantly correlated with a shorter free-time disease and overall survival, whereas in patients with ovarian or endometrial cancer this phenomenon was associated with tumor aggressiveness and a degree of chemoresistance to various antitumor drugs such as anthracyclines, cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 152 publications
4
91
0
8
Order By: Relevance
“…Cathepsin proteases have been implicated in numerous pathologies, including inflammatory processes, 40 Alzheimer's disease, 41,42 and metastasis of tumor cells. [43][44][45][46] Both cathepsins, cath-D and cath-L, produced by all transfectants studied are reported to be active in human thyroid carcinoma tissues. 46 -48 The significant up-regulation in the production and secretion of cath-L forms in RLN2 transfectants correlated with an enhanced elastinolytic activity and the ability to invade elastin matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin proteases have been implicated in numerous pathologies, including inflammatory processes, 40 Alzheimer's disease, 41,42 and metastasis of tumor cells. [43][44][45][46] Both cathepsins, cath-D and cath-L, produced by all transfectants studied are reported to be active in human thyroid carcinoma tissues. 46 -48 The significant up-regulation in the production and secretion of cath-L forms in RLN2 transfectants correlated with an enhanced elastinolytic activity and the ability to invade elastin matrices.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In contrast, pCD (the proform) is overexpressed (2-to 50-fold) in cancerous conditions and its resultant hypersecretion is known to cause enhanced proliferation and neoplastic transformation in various malignancies. [29][30][31] The present study employs the powerful tool of RNAi to determine the effects of long-term knock-down of pCD on cancer progression and thus evaluates the therapeutic efficacy of pCD-shRNA under cancerous conditions. Targeting pCD with antibodies, hammerhead ribozymes and antisense oligonucleotides has been earlier reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several years later, the first clinical studies found pCD/CD related to metastasis-free survival and disease-free survival in breast cancer patients [168,169]. Since then, numerous clinical studies reported an association between pCD/CD level and tumor size, tumor grade, tumor aggressiveness, incidence of metastasis, prognosis, and a degree of chemoresistance in variety of solid tumors including neuroblastoma, glioma, melanoma, endometrial and ovarian tumors, colorectal carcinoma, head and neck tumors, thyroid tumors, pancreatic tumors, lung carcinoma, liver tumors, bladder carcinoma, prostate tumors and gastric carcinoma [25,170,171]. It should be noted, however, that conflicting results were obtained which may reflect the different methodology used for pCD/CD quantification, patients and diagnosis selection, and the length of follow-up period [25,172,173].…”
Section: Cancermentioning
confidence: 99%
“…Since then, numerous clinical studies reported an association between pCD/CD level and tumor size, tumor grade, tumor aggressiveness, incidence of metastasis, prognosis, and a degree of chemoresistance in variety of solid tumors including neuroblastoma, glioma, melanoma, endometrial and ovarian tumors, colorectal carcinoma, head and neck tumors, thyroid tumors, pancreatic tumors, lung carcinoma, liver tumors, bladder carcinoma, prostate tumors and gastric carcinoma [25,170,171]. It should be noted, however, that conflicting results were obtained which may reflect the different methodology used for pCD/CD quantification, patients and diagnosis selection, and the length of follow-up period [25,172,173]. Studies dealing with pCD/CD diagnostic and prognostic value in cancer are complicated by the fact that there are several forms of CD in a cell at the same time -pCD, intermediate enzymatically active CD and mature heavy and light chain CD (Fig 2).…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation